Possible association between subtypes of dry eye disease and seasonal variation - Ayaki M (Dove Medical Press, 2017)
Masahiko Ayaki, Motoko Kawashima, Miki Uchino, Kazuo Tsubota, Kazuno Negishi Department of Ophthalmology, Keio University, Shinjuku, Tokyo, Japan Purpose: The purpose of this study was to evaluate the influence of seasons on the signs and symptoms of dry eye disease (DED). Methods: This is a cross-sectional, case-control study, and participants were non-DED subjects (n=1,916, mean age 54.4±14.4 years) and DED patients (n=684, 54.2±12.1 years) visiting six eye clinics at various practices and locations in Japan. We evaluated the signs and symptoms of DED and the seasons with the most severe results were compared to those with the least severe results in both groups. Main outcome measures were differences in the severity of the signs and symptoms of DED between the most and least severe seasons. Results: The majority of DED symptoms were most severe during spring and least severe in summer. Significant differences between these two seasons were found for irritation (P=0.001), pain (P=0.007), blurring (P=0.000), and photophobia (P=0.007) in the DED group. Superficial punctate keratopathy (P=0.001) and tear break-up time (BUT; P=0.000) results also indicated that DED was most severe in spring. In contrast, fewer patients had low Schirmer test results in spring, although this was not statistically significant (P=0.061). Conclusion: Our results demonstrated that the severity of DED is seasonal, which may explain the increase of short BUT-type DED cases observed in spring when air pollen counts are highest. Keywords: dry eye disease, seasonality, tear break-up time, cornea, ocular surface, tear production, hay fever, air pollen, allergic conjunctivitis